Peningkatan Hasil Belajar Kelas X SMA Katolik Sang Timur Yogyakarta Materi Kesetaraan Laki-laki dan Perempuan melalui Problem Based Learning - Vincentius Bintarti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This classroom action research (CAR) was carried out to improve student learning outcomes using the Problem Based Learning (PBL) learning model. Students at SMA K Sang Timur Yogyakarta come from Sabang to Merauke with varying levels of ability in terms of cognitive, attitudes and skills. Therefore, creative learning is implemented through the Problem-Based Learning model, which activates students in analyzing and solving problems that are appropriate to the context of their lives. This research aims to find out how to apply the Problem Based Learning (PBL) model to improve learning outcomes. Additionally, it aims to analyze and measure the improvement of student learning outcomes after applying the Problem Based Learning (PBL) learning model, especially the material on equality between men and women. Meanwhile, according to the results of the research conducted, there was an increase in the assessment of summative learning outcomes 1 in cycle 1 to summative outcomes 2 in cycle II. In cycle 1 the average score was 67.3 and the average in cycle II reached 83, with a total of 20 students.